Trajectories of Ethnic–Racial Identity and Autonomy Among Mexican‐Origin Adolescent Mothers in the United States. Issue 6 (9th October 2015) - Umaña‐Taylor, Adriana J.; Updegraff, Kimberly A.; Jahromi, Laudan B.; Zeiders, Katharine H.
Abstract : This study examined trajectories of ethnic–racial identity (ERI) and autonomy development among Mexican‐origin adolescent females in the United States ( N  =   181; M age at Wave 1 = 16.80 years, SD  = 1.00) as they transitioned through the first 5 years of parenthood. Trajectories of ERI and autonomy also were examined in relation to psychosocial functioning. Unconditional latent growth models indicated significant growth in autonomy, ERI resolution, and ERI affirmation from middle to late adolescence. Conditional latent growth models indicated that autonomy and ERI exploration growth trajectories were positively associated with psychosocial adjustment. Although adolescent mothers are experiencing transitions that are not normative during adolescence, they also engage in normative developmental processes, and their engagement in such processes is linked with better adjustment.